The diversity of Russian estuaries and lagoons exposed to human influence - Kosyan, R. D. (Springer, 2017)
This volume describes the complex characteristics of almost all Russian coastal estuaries systematized in the following regions: the coasts of the White Sea, the Barents Sea, the Kara Sea, the Laptev Sea, the East Siberian Sea, the Chukchi Sea, the Black Sea, the Sea of Azov, the Baltic Sea, the Sea of Okhotsk, the Sea of Japan and the Bering Seas. The part on the Baltic Sea includes a detailed description of the Kaliningrad coast and the Gulf of Finland. Apart from the geology and morphology, this book also looks at the anthropogenic effects on shores as well as at hydrological conditions, local climate and water level characteristics, and at economic use of lagoons.
Includes index.
Keywords: Estuarine ecology -- Russia (Federation); Estuarine hydrology -- Russia (Federation); Estuarine health -- Russia (Federation); Estuaries -- Russia (Federation); Estuaries -- Russia (Federation) -- Hydrodynamics.; Lagoons -- Russia (Federation); Russia (Federation); elektronické knihy; electronic books